PENGARUH PROMOSI DAN DISKON TERHADAP KEPUTUSAN PEMBELIAN TIKET PESAWAT DI TIKET.COM - Yulia, Nova; Isyanto, Puji (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This research aims to analyze the influence of promotions and discounts on decisions to purchase airline tickets at Tiket.com. Furthermore, it is hoped that the benefits of this research will increase knowledge and insight for the marketing management study program at Buana Perjuangan University Karawang. This article uses a sample of 30 students from Buana Perjuangan University Karawang who use the Tiket.com application. This research is descriptive in nature using quantitative methods using statistics. The research results show that promotions and discounts influence purchasing decisions. Therefore, research findings show that promotions have a significant influence on purchasing decisions at Tiket.com and will increase. Discounts given on airline tickets have also been proven to have a significant impact on purchasing decisions, increasing consumer interest in Tiket.com. Therefore, promotions and discounts are important elements that influence the decision to purchase airline tickets at Tiket.com.